Atypical Cutaneous Manifestations in Adult Onset Still’s Disease - Champa Nataraja; Hedley Griffiths (Case Reports in Rheumatology)
Adult Onset Still’s Disease (AOSD), an adult variant of systemic onset juvenile idiopathic arthritis, is a rare systemic inflammatory disorder of unknown aetiology. The rarity of this disease is associated with low index of suspicion and delayed diagnosis in patients suffering from it and in the presence of atypical features the diagnosis can be further challenging. This is a case report on a 24-year-old woman, who was a diagnostic dilemma for 2 years due to the nonspecific symptoms of recurrent fever, generalized maculopapular persistent pruritic and tender rash, and polyarthralgia. She was initially diagnosed as leukocytoclastic vasculitis on a skin biopsy and was managed by a dermatologist with various medications including NSAIDs, hydroxychloroquine, dapsone, colchicine, cyclosporine, and high doses of oral steroids with minimal response. Subsequently, she has had multiple admissions with similar symptoms with raised inflammatory markers and negative septic workup. On one occasion, her iron study revealed hyperferritinaemia which led to the suspicion of AOSD. Once the rheumatic fever and infectious, malignant, autoimmune, and lymphoproliferative disorders were excluded, she was diagnosed as probable AOSD and managed successfully with IL-1 (interleukin-1) receptor antagonist, Anakinra, with remarkable and lasting response both clinically and biochemically.